Energy migration processes in phosphate nanocrystals: size and dimensionality dependence - Kononets, N.V.; Seminko, V.V.; Maksimchuk, P.O.; Bespalova, I.I.; Klochkov, V.K.; Malyukin, Yu.V. (Физика низких температур, 2018)
Peculiarities of electronic excitation energy migration in phosphate nanocrystals with three-dimensional (EuPO₄) and one-dimensional (EuP₃O₉) arrangement of regular ions under variation of concentration of both energy traps (Nd³⁺ ions) and scattering centres (La³⁺ ions) are discussed in the paper. Processes of energy migration in both EuPO₄ and EuP₃O₉ nanocrystals are phonon-assisted ones due to absence of resonance between energy levels of adjacent Eu³⁺ ions. The distance of energy migration for both EuPO₄ and EuP₃O₉ nanocrystalswas found to be equal to tens of nanometres, however, for EuPO₄ nanocrystals energy migration leads to stronger quenching of Eu³⁺ luminescence. For 10 nm EuPO₄ nanocrystals sufficient hampering of energy migration isobserved due to the depletion of the low-energy phonon spectrum as a result of the phonon confinement effect.